2023
DOI: 10.1002/pssa.202200882
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of NiOx/Poly‐Si Contact Performance by Insertion of an Ultrathin Metallic Ni Interlayer

Abstract: Nickel oxide (NiOx$\left(\text{NiO}\right)_{x}$) is a promising hole transport material for perovskite/Si tandem solar cells. Various silicon cell architectures may be used as bottom cells. The polycrystalline (poly‐Si) p+false/n+$\left(\text{p}\right)^{+} / \left(\text{n}\right)^{+}$ tunnel diode is expected to be a high‐efficiency interconnection scheme between the two subcells of monolithic tandems in p‐i‐n configuration with a high thermal budget, excellent passivation properties, and low contact resistivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…As the oxidation time increased, Ti within the SiO X gradually diffused toward the Si ( Figure 2 d) and reacted with the Si atoms to form TiSi 2 ( Figure 2 e). Recently, Lange et al 39 reported a similar atomic distribution by annealing Ni to form nickel silicide above the poly-Si layer, stating that the metallic Ni atoms inside the SiO X layer serve as a pathway for current flow.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…As the oxidation time increased, Ti within the SiO X gradually diffused toward the Si ( Figure 2 d) and reacted with the Si atoms to form TiSi 2 ( Figure 2 e). Recently, Lange et al 39 reported a similar atomic distribution by annealing Ni to form nickel silicide above the poly-Si layer, stating that the metallic Ni atoms inside the SiO X layer serve as a pathway for current flow.…”
Section: Resultsmentioning
confidence: 91%
“… 38 NiSi, formed between NiO X and n + poly-Si, assists carrier transportation, resulting in ohmic current–voltage ( I – V ) characteristics. Lange et al 39 also used a NiSi interlayer to improve the NiO X /poly-Si contact properties. However, the performances of tandem devices with silicide-based interlayers have not yet been reported.…”
Section: Introductionmentioning
confidence: 99%